Classification and Assessment of Aridity Over Pakistan Provinces (1960-2009) - Haider, Sajjad; Adnan, Shahzada (International Journal of Environment, 2014)
Due to rapid growth of population, massive deforestation and anthropogenic activities, noticeable change in climate conditions is being observed in Pakistan. Increased aridity due to climate change is a growing environmental problem of the agricultural country like Pakistan. It is essential to assess and monitor aridity to combat the probable land degradation and drought desertification. Identification of arid and semi arid regions on climatic basis is the first essential step in any project of land reclamation for agricultural and other purposes. A geographic information system is used in this paper for the assessment of aridity in Pakistan from long term climatic data of fifty years (1960-2009) collected from fifty four stations situated in the country. In the delineation of climatic zones and delimitation of their boundaries, five well known aridity models viz. De Martonne Aridity index, Erinc Aridity index, Thornthwaite Precipitation Effectiveness index, UNESCO Aridity index and Thornthwaite Moisture index are utilized for this purpose. The study shows that southern parts of the country are dry and more vulnerable to drought while the northern parts have variable types of climate. Almost 75 to 85% of the total area of the country is arid in which most part lies in the south while less than 10% area is humid lies in the north of the country. This study will be a good predicator for agricultural scientist, agronomist and hydrologist to plan according the climate of the region. DOI: http://dx.doi.org/10.3126/ije.v3i4.11728 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page : 24-35